2022
DOI: 10.1002/prep.202100384
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Anisotropy of 1,3,5‐Triamino‐2,4,6‐Trinitrobenzene as a Function of Temperature and Pressure: A Molecular Dynamics Study

Abstract: The equation of state of the triclinic compound 1,3,5‐triamino‐2,4,6‐trinitrobenzene (TATB) as well as its second‐order isothermal elastic tensor were computed through classical molecular dynamics simulations under various temperature and pressure conditions. Hydrostatic pressures similar to previous diamond anvil cell experiments were imposed up to 60 GPa and temperatures chosen between 100 and 900 K in conjunction with the most recent version of an all‐atom fully flexible molecule force field. The isothermal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…One can immediately notice from Table 5 Compared to Rykounov's results, we find that the older FFs predict a number of major (and subtle) differences in the C ij and derived moduli at 0 K and 0 GPa. As was discussed in previous studies, 16,45,46 the Bedrov FF leads to generally smaller magnitude values compared to DFT, especially for inplane longitudinal and shear coefficients that result in low shear and Young's moduli. Coefficients that are underpredicted by the Bedrov FF are generally overpredicted by the revised Gee FF.…”
Section: Solid−solidmentioning
confidence: 62%
See 2 more Smart Citations
“…One can immediately notice from Table 5 Compared to Rykounov's results, we find that the older FFs predict a number of major (and subtle) differences in the C ij and derived moduli at 0 K and 0 GPa. As was discussed in previous studies, 16,45,46 the Bedrov FF leads to generally smaller magnitude values compared to DFT, especially for inplane longitudinal and shear coefficients that result in low shear and Young's moduli. Coefficients that are underpredicted by the Bedrov FF are generally overpredicted by the revised Gee FF.…”
Section: Solid−solidmentioning
confidence: 62%
“…Although TATB is not a meltcastable explosive, the melting point has been estimated at atmospheric pressure both by Stolovy et al 29 in 1983 and by Bowlan et al 30 in 2022, with both reports yielding values near 700 K. Polymorphism in TATB has been the subject of speculation for decades, with several reports 19,31 proposing alternative crystal structures that exhibit layered motifs similar to the Cady and Larson structure. While these transitions have not been verified, a 2019 single-crystal diffraction study by Steele et al 32 identified a high-pressure monoclinic polymorph above ≈4 GPa and reported lattice parameters for it up to 16 GPa. The monoclinic and triclinic packing structures were found to be very similar, and electronic structure calculations indicated that the two structures are essentially isenthalpic, although the free-energy landscape for this transition remains unquantified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme insensitivity of TATB is posited to be caused by the graphite-like layered crystal structure with its intralayer intra- and intermolecular hydrogen bonds and weaker interlayer π-stacked interactions . The pleochroic TATB crystal exhibits pronounced anisotropy in many properties, including thermal expansion, hydrostatic compression, ,, and tensorial elastic mechanical response. , The MSCG/FM procedure under constant ε̂ is expected to better capture the reference highly anisotropic interactions pertinent to the TATB crystal.…”
Section: Application To a Molecular Crystalmentioning
confidence: 99%
“…These mechanisms range from elastic instabilities (when the loading is parallel to the molecular layer plane), pure elastic buckling or twinning, basal homogeneous shear and layer sliding, and out-of-plane dislocations. Efforts have been devoted to the construction of a mesoscopic thermo-mechanical model, where the necessary ingredients for proper coarse graining have been shown to be entirely contained in the directional yield stress surface . The present constitutive law for TATB at the meso-scale includes non-linear anisotropic hyperelasticity depending on an EOS and a phase field by reaction pathway formalism to model twinning. While crystal plasticity is not yet included and will be the object of future work, the model has been validated against one-to-one comparison with atomistic simulations using a variety of deformation setups.…”
Section: Introductionmentioning
confidence: 99%